Voltammetric Determination of Amino Acids Based on the Measurement of Reduction Prepeak of Quinone Caused by Surplus Acid after Neutralization. Issue 12 (23rd October 2018) - Kotani, Akira; Kitamura, Kanae; Kusu, Fumiyo; Yamamoto, Kazuhiro; Hakamata, Hideki
Abstract: In the voltammetric reduction of quinone, such as 3, 5‐di‐ tert ‐butyl‐1, 2‐benzoquinone (DBBQ), in the presence of HCl, a reduction prepeak of DBBQ caused by HCl can be observed on a voltammogram. Here, we have shown that the prepeak height of DBBQ is linearly decreased with increasing concentrations of amino acid in an electrolyte solution when this voltammetry is performed after neutralization between amino acids and excess HCl. This finding is based on a concept of acid‐base back titration of amino acids with excess HCl where surplus HCl gives a reduction prepeak of DBBQ. In this study, the reduction behaviors of DBBQ in the presence of amino acids and HCl have been provided to develop a novel electroanalytical method for the determining of amino acids. Electrochemical detection of 20 kinds of α‐amino acids, including less electroactive ones, has been achieved using a bare plastic formed carbon working electrode. Moreover, a flow injection analysis with electrochemical detection system using a glassy carbon working electrode is developed based on the present detection principle, and it has been applied to the determination of glutamine in an L‐glutamine granulated powder. Abstract :